MENINGKATKAN HASIL BELAJAR SISWA MELALUI PENERAPAN STRATEGI CROSSWORD PUZZLE DI MADRASAH IBTIDAIYAH MIFTAHUL ULUM KABUPATEN MEMPAWAH - Neneng Sulasmi (CV. ADIBA AISHA AMIRA, 2024)
The purpose of this study is to improve the learning outcomes of Aqidah Akhlaq in Grade IV of MI Miftahul Ulum. This research uses a qualitative approach. The type of research used is Classroom Action Research (CAR) which consists of two cycles, namely Cycle I and Cycle II, where each cycle is a series of activities consisting of four stages, namely the planning stage, the implementation stage, the observation stage and the reflection stage. The data collection techniques used were written tests, interviews, observations and documentation. The subjects of this study were 30 fourth-grade students, consisting of 16 boys and 14 girls. Based on the results of this study, it shows that the process of learning Aqidah Akhlaq by applying the crossword puzzle strategy can help students understand the material easily, making learning more enjoyable and involving students to be more active in the learning process. The students' learning outcomes have improved greatly in each cycle, as seen from the average score for each cycle, which has increased. This can be seen from the comparison of student learning outcomes before the implementation of the crossword puzzle strategy, there are still many students who have not reached the minimum learning standards, as seen from the pre-cycle average score of 58.33. Then after the implementation of the crossword puzzle strategy, student learning outcomes increased, as seen from cycle I with an average of 85.33. Meanwhile, cycle II also increased from the results of cycle I, which was an average of 92.33. So, the results of this study can be concluded that the crossword puzzle strategy can improve the learning outcomes of fourth grade students at Miftahul Ulum Islamic Elementary School in the 2024/2025 academic year.